1997
DOI: 10.1016/s0014-5793(97)00196-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a new receptor for galanin

Abstract: Galanin (GAL) is a widely distributed neuropeptide with diverse biological effects including modulation of hormone release, antinociception and modification of feeding behavior. Its effects are mediated through G-protein-coupled receptors (GPCR) for which only a single type has been cloned, GAL receptor 1 (GALR1). We describe the cloning of a second galanin receptor type, GALR2, from rat hypothalamus. The GALR2 amino acid sequence is 38% identical to GALR1 and is pharmacologically similar to GALR1 when express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
148
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 18 publications
5
148
0
1
Order By: Relevance
“…We report here the isolation by expression cloning and the pharmacological characterization of a novel galanin receptor from a rat hypothalamic cDNA library. The new galanin receptor subtype, termed GALR2, has the same predicted amino acid sequence as the galanin receptor cDNA recently described by Howard et al (22) which was reported to have a pharmacological profile similar to the GALR1 receptor. We provide evidence here that GALR2 is distinct from GALR1 in both its pharmacological profile and its primary signal transduction pathway.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…We report here the isolation by expression cloning and the pharmacological characterization of a novel galanin receptor from a rat hypothalamic cDNA library. The new galanin receptor subtype, termed GALR2, has the same predicted amino acid sequence as the galanin receptor cDNA recently described by Howard et al (22) which was reported to have a pharmacological profile similar to the GALR1 receptor. We provide evidence here that GALR2 is distinct from GALR1 in both its pharmacological profile and its primary signal transduction pathway.…”
mentioning
confidence: 63%
“…In particular, the rat 5-HT 7 receptor (31, 32) contains an intron in the same location we now report for GALR2, within the A(G/G) codon for the highly conserved amino acid arginine at the end of TMIII. Recently, the cloning of a galanin receptor with the same predicted amino acid sequence was described by Howard et al (22), who isolated both intron-containing and correctly spliced cDNAs. Interestingly, the nucleotide sequence of the 490-base pair intron reported by Howard et al (22) is contained entirely within the ϳ1-kb intron described here, suggesting that the intron itself can be alternatively or incompletely spliced.…”
Section: Resultsmentioning
confidence: 99%
“…Three subtypes of galanin receptors have been cloned, GalR1 (Habert-Ortoli et al 1994;Burgevin et al 1995;Parker et al 1995) GalR2 (Howard et al 1997;Smith et al 1997;Wang et al 1997a) and GalR3 (Wang et al 1997b;Smith et al 1998), which all belong to the superfamily of G-protein-linked receptors. The autoradiographic receptor binding studies have indicated moderate galanin R1 and R2 receptor binding in the DRN .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, cDNAs encoding a second rat GALR subtype, termed GALR2, was isolated and characterized pharmacologically Howard et al, 1997;Wang et al, 1997a). Recently a third rat GALR, designated GALR3, has also been identified from a rat hypothalamic cDNA library (Wang eta!., 1997b).…”
Section: F Kolakowski Jr Et Almentioning
confidence: 99%